Hepatitis C Prevalence in Patients Attending a Free Cataract Surgery Camps in Southern areas of Khyber Pakhtunkhwa, Pakistan - Shafi Ullah, Rabeea Zia, Sajad Ahmad, Noor ul Basir, Mohamed Gamal Elsehrawy, Alok Dubey (Pakistan Journal of Medical & Health Sciences, 2022)
Hepatitis C is a major public health concern in developing countries. Early research has shown that the prevalence of HCV is extremely high. This has raised questions regarding how preventive measures will be distributed and implemented in the future on a larger scale. This study aimed to investigate the prevalence of Hepatitis C in people who were getting cataract surgery at a free eye camp as a potential occupational hazard for healthcare workers. Taking place from the 15th to the 18th of October 2021 in the Southern areas of Khyber Pakhtunkhwa, Pakistan, free eye camps were hosted at the Welfare Hospitals. In the study, all the patients scheduled for cataract surgery were included. For the screening of these patients for antibodies to Hepatitis C, the Kit Method was utilised. All the information was recorded using a methodical proforma that was followed. The data was analysed to estimate the average age, gender distribution, and prevalence of Hepatitis C in the population. A total of 106 patients scheduled for cataract surgery were tested for hepatitis C. The results were negative. A total of 36 (34 percent) of the patients tested positive for Hepatitis C, with the average age being 61 years old. A basic infection control protocol must be always maintained, even if free eye camps are a fantastic activity for restoring sight to the visually impaired. The development and implementation of legal protocols for these camps should be the responsibility of the government. In addition to posing a concern for the public, this also poses a threat to health-care workers